2013
DOI: 10.3791/50768
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based Assay Protocol for the Prognostic Prediction of Idiopathic Scoliosis Using Cellular Dielectric Spectroscopy

Abstract: This protocol details the experimental and analytical procedure for a cell-based assay developed in our laboratory as a functional test to predict the prognosis of idiopathic scoliosis in asymptomatic and affected children. The assay consists of the evaluation of the functional status of Gi and Gs proteins in peripheral blood mononuclear cells (PBMCs) by cellular dielectric spectroscopy (CDS), using an automated CDS-based instrument, and the classification of children into three functional groups (FG1, FG2, FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In this study, we are proposing the first hypothesis relating brace outcome and intrinsic cellular profile connected to the roles of GPCRs as mechanosensors. This study evaluated patient outcomes based on three biological endophenotypes defined by the differential hypofunctionality of Gi alpha subunits [10,11] as initially evidenced by a differential dysfunction of melatonin signal transduction [7][8][9]. Differences between the three endophenotypes acquired through a cell-based assay were identified in the outcomes of brace treatment both for final Cobb and progression criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we are proposing the first hypothesis relating brace outcome and intrinsic cellular profile connected to the roles of GPCRs as mechanosensors. This study evaluated patient outcomes based on three biological endophenotypes defined by the differential hypofunctionality of Gi alpha subunits [10,11] as initially evidenced by a differential dysfunction of melatonin signal transduction [7][8][9]. Differences between the three endophenotypes acquired through a cell-based assay were identified in the outcomes of brace treatment both for final Cobb and progression criteria.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were classified according to their biological endophenotype, FG1, FG2, or FG3. The endophenotypes were measured by CDS using PBMCs as previously described [9,10].…”
Section: Cellular Dielectric Spectroscopy (Cds) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported that different characteristics can be used for the prediction of severe spine deformity, such as clinical [ 27 ], radiographic [ 28 ], physiologic [ 29 ], biochemical [ 30 ], genetic [ 31 ], and combinatorial parameters [ 32 ]. Tan et al [ 21 ] examined 186 AIS patients and noted that curve magnitude more than 30 degrees at first session was the most important predictive factor for curve progression.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin secretion is stimulated by several Gs-coupled receptors and inhibited by many Gicoupled and Gq receptors [31]. Given that a Gisignalling dysfunction has been reported in AIS [32], it is conceivable that Gi protein hypofunctionality in AIS could contribute to the elevation of plasma ghrelin levels in AIS patients.…”
Section: Discussionmentioning
confidence: 99%